ETIKA BERNIAGA DALAM TINJAUAN HUKUM ISLAM - Irsal Irsal (Qiyas : Jurnal Hukum Islam dan Peradilan, 2021)
Abstract: Commerce is a human activity to fulfill their needs. With the development of science and technology, commerce has progressed very rapidly according to the needs and demands of the times. Human commerce also varies, ranging from small industry to large industry, goods and service companies, agricultural businesses, and others. Humans are seen to be so in love with wealth, that problems, disputes and disputes often occur which give rise to fierce and unhealthy competition that harms each other. The Al-Qur`an and hadith as guidelines for Muslims have provided rules for how humans can acquire wealth, because in fact human activity in obtaining wealth is not only related to fellow human beings, but in essence is also related to Allah SWT.Keywords: Business Ethics, Islamic Law Abstrak: Perniagaan merupakan aktivitas manusia untuk memenuhi kebutuhan hidupnya. Dengan berkembangnya ilmu pengetahuan dan teknologi, perniagaan mengalami kemajuan yang sangat pesat sesuai dengan kebutuhan dan tuntutan zaman. Perniagaan yang dilakukan manusia pun bermacam- macam, mulai dari industri kecil sampai industri besar, perusahaan barang dan jasa, usaha pertanian, dan lain-lain. Manusia dipandang begitu cinta kepada harta, sehingga sering terjadi permasalahan, perselisihan, dan persengketaan yang menimbulkan persaingan sengit dan tidak sehat yang saling membahayakan. Al-Qur`an dan hadits sebagai pedoman umat Islam telah memberikan aturan bagaimana manusia dapat memperoleh harta, karena sesungguhnya aktivitas manusia dalam memperoleh harta tidak hanya berhubungan dengan sesama manusia, tetapi hakikatnya juga berhungan dengan Allah SWT.Kata kunci : Etika Berniaga, Hukum Islam